DETECTION OF LAYER BOUNDARIES IN WELLS USING MULTI-ELECTRODE RESISTIVITY DATA - Weller A.; Furche M.; Schon J.H. (My University, 2003)
Multi-electrode resistivity data can be used to compute the measurable response for conventional and focused configurations. Some of them are appropriate for detecting layer boundaries. Three different configurations are investigated concerning their suitability for identification of bed boundaries: a second difference configuration, a combined lateral configuration and a Laterolog-7. A normalized apparent resistivity is used as an indication parameter for detection of horizontal bed boundaries for the first two configurations. For the Laterolog-7, the curve of the logarithm of the quotient of the two current ratios is used. The boundaries are indicated by extreme values in the relevant curves. The ability of layer identification of the three configurations is tested with synthetic and measured data. The parameter curves provide different information: the peaks indicate the presence of a layer boundary, the sign of the peak (positive or negative) indicates the type of transition (resistive-conductive or conductive-resistive). The Laterolog-7 shows the best results concerning resolution and accuracy. It yields additional information as the absolute values are related to the resistivity contrast of the adjacent beds. The combined lateral configuration also proved to be suitable for detection of layer boundaries. The second difference configuration only indicates the transition from conductive to resistive layers. It is severely affected by noisy data.
Keywords: BOREHOLE GEOPHYSICS; ELECTRICAL RESISTIVITY; LAYER BOUNDARIES; NUMERICAL TECHNIQUES